(untitled)
Two methods were used in the prospection study of streams and recent alluvium in the western parts of the Kratovo-Zletovo volcanic area (BLEG and stream sediments). The research and samples analysis by the BLEG method determined gold content in all samples in the locality Borović, within the range from 0.00031 to 0,248 ppm Au, and in the locality Plavica gold content ranged from 0.00047 to 0,0667 ppm Au. Examined and studied stream sediments from localities of the recent alluvium Borović (Povišnica river) and Plavica localities determined characteristic geochemical associations of elements that were statistically processed that obtained appropriate groups of equivalent elements, which form cluster systems. Cluster analysis identified associations that can be divided into ore associations and associations originating from rocks, which built adjacent setting around the mineralization. From ore associations in the locality Borović were determinated three element associations:[(Y-Co)-(Ta-Nb)]-Ni; ║∫[(Sn-Pb)-S)-Ga]-Bi]-[(Te-In)-Ag]-As∫-(U-Sb)║; [(Cd-Zn)-(Au-Cu)]-(Ge-W)]-(Fe-V)]